2014
DOI: 10.2174/1872208309666140904113615
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics in Psychiatry: Implications for Practice

Abstract: Psychotropic medications are used for numerous psychiatric and neurologic disorders, and are associated with in some cases life-threatening adverse effects, high acquisition costs, stringent monitoring requirements, and potential interactions with other medications. Because of the risks of adverse effects and need for adherence, risk mitigation strategies are being implemented to protect consumers. An understanding of receptor activities, cytochrome P450 2D6 and 2C19 metabolism, overlapping pharmacology, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…Sex was not found to be a risk factor in our sample, although some studies indicate a higher risk among women. 7,38 Recent reviews point that the cause of agranulocytosis is not dose related or correlated with a certain ethnic group, 39 although some earlier studies suggested increased or lower risk in certain populations (higher in Scandinavians, Ashkenazic Jews, lower in Chinese). 40 No relation with clozapine dose was found in the present study, and to our knowledge, special susceptibility for CAA does not exist for Turkish patients.…”
Section: Discussionmentioning
confidence: 99%
“…Sex was not found to be a risk factor in our sample, although some studies indicate a higher risk among women. 7,38 Recent reviews point that the cause of agranulocytosis is not dose related or correlated with a certain ethnic group, 39 although some earlier studies suggested increased or lower risk in certain populations (higher in Scandinavians, Ashkenazic Jews, lower in Chinese). 40 No relation with clozapine dose was found in the present study, and to our knowledge, special susceptibility for CAA does not exist for Turkish patients.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] With regards to TRS and SRS genetic components, variability in cytochrome P450 (CYP) enzyme activities have been described as significant in influencing CLZ bioavailability. [15][16][17] CYP3A4 and CYP1A2 are primarily responsible for the formation of N-desmethylclozapine, 18,19 with CYP2C19 playing a role and CYP2C9 and 2D6 playing more modest roles. 20 In light of these functions, our group previously observed CYP1A2*1F polymorphism associations with SRS, 9 thereby shedding some light on the relevance of CYP-genetic polymorphisms in CLZ responses.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical, demographic and genetic specific profiles could contribute in different ratios to significant interpatient variability noticed in both therapeutic efficacy and adverse drug reactions (ADR) (Moore, Hill & Panguluri, 2014;Tauser 2012). "Antipsychotic Trials of Intervention Effectiveness" (CATIE) estimates that over 70% of chronic schizophrenia patients stopped the antipsychotics because of sub-optimal efficacy or safety and treatment-resistant schizophrenia (TRS) affects ~30% of patients (Eum, Lee, & Bishop, 2016).…”
Section: Pharmacogenomics: the Promise Of Personalized Psychotropic Tmentioning
confidence: 99%